2003
DOI: 10.1046/j.1460-9568.2003.02445.x
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory learning modifies the expression of odour‐induced oscillatory responses in the gamma (60–90 Hz) and beta (15–40 Hz) bands in the rat olfactory bulb

Abstract: This study addressed the question of the possible functional relevance of two different oscillatory activities, beta and gamma (15-40 and 60-90 Hz, respectively) for perception and memory processes in olfactory areas of mammals. Local field potentials were recorded near relay olfactory bulb neurons while rats performed an olfactory discrimination task. Signals reflected the mass activity from this region and characteristics of oscillatory activities were used as an index of local synchrony. Beta and gamma osci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(153 citation statements)
references
References 49 publications
(70 reference statements)
10
143
0
Order By: Relevance
“…As shown previously (Ravel et al, 2003), odor sampling induced opposite changes in ␥ (60 -90 Hz) and ␤ (15-40 Hz) frequency bands. The two rhythms never coexisted in response to odorant stimulation.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…As shown previously (Ravel et al, 2003), odor sampling induced opposite changes in ␥ (60 -90 Hz) and ␤ (15-40 Hz) frequency bands. The two rhythms never coexisted in response to odorant stimulation.…”
Section: Discussionsupporting
confidence: 80%
“…More recently, in mammalian OB, both surface and deep local field potential (LFP) recordings revealed that odor sampling enhanced oscillatory activity in ␤ frequency . This response was found for behaviorally relevant odors (Zibrowski and Vanderwolf, 1997;Chabaud et al, 2000), odors experimentally associated with a reward (Boeijinga and Lopes da Silva, 1989;Ravel et al, 2003), and after repeated presentations of the same odor (Gray and Skinner, 1988b;Chabaud et al, 2000).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Oscillations are sensitive to tetanization of excitatory afferents from the olfactory receptor neurons (Friedman and Strowbridge, 2003), actions exerted by neuromodulatory systems (Gray et al, 1986;Gervais et al, 1990), or feedback from the piriform and the entorhinal cortices (Haberly and Price, 1978). This modulation can take part in several processes such as memory [in insects (Stopfer and Laurent, 1999) and in mammals (Ravel et al, 2003)] and habituation (Gray and Skinner, 1988). In line with this, granule cells, among the key elements for generating LFP oscillations, undergo a permanent renewal (Altman, 1969).…”
Section: ␥ Oscillations and Olfactory Information Processingmentioning
confidence: 95%
“…There is now a large and rapidly expanding literature that describes the spectral content of electrical activity in different cognitive states, in different tasks, and in different parts of the brain Tallon-Baudry, 2004). These studies also document how spectral content can change over the process of learning (Ravel et al, 2003). Finally, many studies have documented how spectral content differs from controls in a variety of mental disorders (Phillips and Silverstein, 2003;Uhlhaas and Singer, 2006).…”
Section: Classical Rhythms and Their Discontentsmentioning
confidence: 84%